Peran Struktur Modal dan Profitabilitas dalam Meningkatkan Nilai Perusahaan Sektor Perkebunan Indonesia - Rahmazaniati, Linda; Rahmadani, Ika; Maulina, Rina; Vonna, Sari Maulida; Husen, Tamitha Intassar (Akbis: Media Riset Akuntansi dan Bisnis, 2024)
This study aims to examine and analyze the influence of capital structure and profitability on the value of companies in the plantation sector. Using a quantitative approach, a sample of 15 agricultural sector companies was selected through purposive sampling. The data analysis method employed multiple. linear regression using secondary data from the companies' financial reports. The testing results using SPSS 27 revealed that, partially, the capital. structure, as proxied by the Debt. to Equity Ratio (DER), does not have an effect on the value of the company. Profitability does influence the value of the company. Both capital structure and. profitability simultaneously affect the value of the company. The R² coefficient test result was 0.612, indicating that 61.2% of the independent. variables' ability to explain the dependent. variable is quite significant.